Professional tennis players suffer high prevalence of shoulder alterations during the season: a possible tennis shoulder syndrome - López-Vidriero Tejedor, R.; Laver, L.; López-Vidriero Tejedor, E. (Knee surgery, Sports Traumatology. Arthroscopy, 2023)
Purpose: To analyze the shoulder alterations of professional tennis players during the competition season and to compare the differences between their dominant vs. non-dominant shoulders, as well as gender and age differences. Methods: Two-hundred and seventy shoulders of (78 men and 57 women) professional active tennis players were assessed during 3 ATP and WTA tournaments. Main variables studied: long head of biceps (LHB) tenderness and synovitis; glenohumeral internal rotation deficit (GIRD), total range of motion (TRM), external rotation (ER) and scapular dyskinesis (DK). Secondary variables: shoulder dominance, gender, age, training hours, ranking, type of backhand. LHB tenderness and synovitis were assessed by clinical and ultrasound examination, TRM with goniometer and DK by dynamic observation. Results: LHB tenderness of the dominant shoulder was present in 35% of all players, being more prevalent in women (47.4%) than men (26.9%) p = 0.023. LHB synovitis of the dominant shoulder was present in 20.2% of all players without difference between genders (n.s). High prevalence of GIRD was found in both dominant (87.4%) and non-dominant (56.3%) shoulders, being more prevalent in the dominant shoulder p = 0.00005. TRM was decreased in both dominant (144.5° ± 20.2°) and non-dominant shoulders (161.2° ± 18.9°) p = 0.00005. ER was normal in dominant (93.8° + /9.3°) and non-dominant shoulders (93.4° + /8.4°) (n.s). DK was present in 57.7% of dominant and 45.9% of non-dominant shoulders (n.s). The combination of LHB alterations, GIRD and DK in the dominant shoulder was present in 13.3% of the participants. There were no significant differences between younger (< 22years) vs older players (= 22years). Conclusion: Professional tennis players actively playing suffer a high prevalence of LHB inflammation, GIRD, scapular dyskinesis and decreased TRM in their dominant and non-dominant shoulders. The LHB is a significant cause for anterior shoulder pain in this population. Women suffer more LHB tenderness than men. Young players are as affected as older players.